2019
DOI: 10.1186/s13717-019-0183-7
|View full text |Cite|
|
Sign up to set email alerts
|

Variable retention forestry in European boreal forests in Russia

Abstract: We explored whether, and to what extent, variable retention (VR) forestry has been applied in European boreal forests in northwestern Russia. Our survey revealed VR since 1910. Between 1910 and the 1960s, the statistics showing how much was retained are largely missing. However, for example, in the 1950s, on a large scale in the Republic of Karelia, up to 200-ha-sized harvesting areas, 18-33%, were retention patches with a mean growing stock of 30-40 m 3 ha −1 . In the fellings defined as "incomplete clear fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The original descriptions of Cajander's and Sukachev's forest types were based on the understorey species composition of mature, unmanaged forests. However, those have become rare in Finland (Kuuluvainen and Gauthier, 2018) as well as in Karelia and adjacent territories (Shorohova et al, 2019). Cajander eventually defined his classification to include variation caused by stand succession as well as management, and it has indeed been shown that the successional stage and the disturbance history of the stand influence the composition of the understorey (Fedorchuk et al, 2005; Uotila et al, 2005; Uotila and Kouki, 2005; Genikova et al, 2012, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The original descriptions of Cajander's and Sukachev's forest types were based on the understorey species composition of mature, unmanaged forests. However, those have become rare in Finland (Kuuluvainen and Gauthier, 2018) as well as in Karelia and adjacent territories (Shorohova et al, 2019). Cajander eventually defined his classification to include variation caused by stand succession as well as management, and it has indeed been shown that the successional stage and the disturbance history of the stand influence the composition of the understorey (Fedorchuk et al, 2005; Uotila et al, 2005; Uotila and Kouki, 2005; Genikova et al, 2012, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to site conditions affecting growth and transport infrastructure, tree data forms the base for dividing a management unit into forest stands with homogenous properties [108]. To mitigate problems caused by forestry intensification for biodiversity conservation retention, forest certification has promoted set-aside of woodland key biotopes, such as paludified forest patches, buffers around water bodies, habitats of red-listed species, as well as of dispersed retention of living trees, snags and dead wood [109,110]. However, Blumröder et al [111] stressed that the effectiveness of stand-scale conservation instruments has to be assessed, with respect to edge effects and secondary dieback of retention trees and patches.…”
Section: Trees In Standsmentioning
confidence: 99%
“…At that time, burnings were an essential method when these countries decided to rapidly transform their forests into even-aged, cultivated stands and to practice modern, intensified forestry. In Russian Karelia, similar prescribed burnings were common in the 1920s and 1930s, but after that, they gradually diminished and were finally forbidden in 1993 (Shorohova et al 2019).…”
Section: Restoration Burningsmentioning
confidence: 99%